S-t=3,s/3+t/2=6 Solve leaniar equation By using substitution method
Answers
Answered by
196
Hi there!
s-t =3 -----(1)
s/3 + t/2 = 6 ----(2)
Therefore the first equation is easy, so we convert it into this form:-
s-t = 3
s = 3 +t -----(3)
Now substituting equation (3) in (2)
3+t /3 + t/2 =6
Now we take the LCM of their denominators..except for the RHS..
2×{3+t/3} + 3×{t/2} = 6
6+2t+3t the whole divided by 6 = 6
6+2t+3t = 6×6
2t+3t = 36
5t = 36-6=30
t = 30/5
t =6 -----(4)
Now substitute (4) in (3)
s = 3+6
s = 9
Hope it helps you..
Thank you..
s-t =3 -----(1)
s/3 + t/2 = 6 ----(2)
Therefore the first equation is easy, so we convert it into this form:-
s-t = 3
s = 3 +t -----(3)
Now substituting equation (3) in (2)
3+t /3 + t/2 =6
Now we take the LCM of their denominators..except for the RHS..
2×{3+t/3} + 3×{t/2} = 6
6+2t+3t the whole divided by 6 = 6
6+2t+3t = 6×6
2t+3t = 36
5t = 36-6=30
t = 30/5
t =6 -----(4)
Now substitute (4) in (3)
s = 3+6
s = 9
Hope it helps you..
Thank you..
aveenarose123:
If it helped u pls mark as brainliest pls
Answered by
208
Answer:
Step-by-step explanation:
Given :-
s – t = 3
s/3 + t/2 = 6
Solution :-
⇒ s – t = 3 ... (i)
⇒ s/3 + t/2 = 6 ... (ii)
From equation (i), we get s = t + 3
Putting this value in equation (ii), we get
⇒ t + 3/3 + t/2 = 6
⇒ 2t + 6 + 3t = 36
⇒ 5t = 30
⇒ t = 30/5
⇒ t = 6 ... (iv)
Putting in equation (iii), we get
⇒ s = 9
Hence, s = 9, t = 6
Similar questions